Cotorsion Dimension of Weak Crossed Products (Communications in Mathematical Research, 2019)
Let $H$ be a finite-dimensional weak Hopf algebra over a field $k$ and $A$ an associative algebra, and $A#_{σ}H$ a weak crossed product. In this paper, a spectralsequence for Ext is constructed which yields an estimate for cotorsion dimension of$A#_{σ}H$ in terms of the corresponding data for $H$ and $A$.
Keywords: weak crossed product; cotorsion dimension; projective resolution